Elements that integrate checklists for safe cardiac surgery (Research, Society and Development, 2022)
Objective: to seek evidence available in the literature on elements that make up checklists for safe cardiac surgery. Methodology: this is an integrative review, carried out between September and October 2020, studies in English, Portuguese and Spanish with a qualitative and quantitative approach that answered the guiding question. Time frame was not used due to the limited number of articles that met the inclusion criteria. This article originated from the research project entitled “Construction and validation of an instrument for care in safe cardiac surgery”, approved by the Research Ethics Committee of the Federal University of Alagoas, and based on the opinion issued under number 15410219.6.0000.5013. Results: the articles included in accordance with the eligibility criteria for the integrative review presented safety elements aimed at surgical specificity, eight articles were found and it was possible to see appropriate items aimed at the surgical safety of cardiac patients. Conclusion: specific items for cardiac surgery were diverse, bringing together clear and objective information regarding safety for cardiac surgical patients.